2018
DOI: 10.1002/bmc.4210
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microdialysis with ultra performance liquid chromatography–mass spectrometry for analysis of tetramethylpyrazine and its interaction with borneol in rat brain and blood

Abstract: Tetramethylpyrazine (TMP) has been widely used in the treatment of ischemic cerebrovascular disease. However, the mechanism of TMP and how to increase its bioavailability need to be further explored. In our study, an in vivo microdialysis sampling technique coupled with ultra-performance liquid chromatography-mass spectrometry method was developed to investigate the pharmacokinetic properties of TMP and its interaction with different doses of borneol (BO) in rats. Linearity of TMP in brain and blood dialysates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…BO can act as an effective adjuvant for delivering TMP to the brain. Studies have shown that the co-administration of BO could significantly increase oral absorption, areas under the concentration-time curve (AUC), and the concentration of TMP in the brain tissue ( Yan-Yu et al, 2007 ; Liao et al, 2018 ; Wu et al, 2018 ).…”
Section: Drug Delivery System Of Tetramethylpyrazinementioning
confidence: 99%
“…BO can act as an effective adjuvant for delivering TMP to the brain. Studies have shown that the co-administration of BO could significantly increase oral absorption, areas under the concentration-time curve (AUC), and the concentration of TMP in the brain tissue ( Yan-Yu et al, 2007 ; Liao et al, 2018 ; Wu et al, 2018 ).…”
Section: Drug Delivery System Of Tetramethylpyrazinementioning
confidence: 99%
“…The brain tissue was homogenated with isotonic buffer solution (pH 7.4) and centrifuge at 10,000 rpm2-4°C, the supernatant was collected in an Eppendorf tube. 100 µl of brain homogenate was mixed with 300 µl of methanol and further centrifuged at 10,000 rpm; 2-4°C, the supernatant was collected and stored in -20°C for HPLC analysis (Wang et al 2011;Feng et al 2017;Liao et al 2018).…”
Section: Plasma/brain Sample Preparationmentioning
confidence: 99%
“…It can enhance the permeability of various membranes, including gastrointestinal mucosa and skin, and even blood-brain barrier [14][15][16][17][18]. Borneol can promote the absorption of Ligustrazine and increase blood flow during ischemia [19]. In the process of studying the pharmacokinetic characteristics of borneol modified tanshinone IIA liposomes in rats, ye x et al found that borneol modified liposomes could significantly increase the maximum plasma concentration and area under the curve of tanshinone IIA during cerebral ischemia-reperfusion [20].…”
Section: Introductionmentioning
confidence: 99%